Light-Emitting Diode for Mitigating Horseshoe Crab (Limulidae) Bycatch of Bottom Gillnet Fishery for Blue Swimming Crab in the Waters of Ambulu Village, Cirebon Regency - Wazir Mawardi; Muhammad Faishal Ashshiddiqi; Zulkarnain; Am Azbas Taurusman; Fis Purwangka (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Mimi, a term for horseshoe crabs (Limulidae), often constitutes an unintended bycatch in blue swimming crab (BSC) fisheries employing bottom gillnet fishing gear. Three horseshoe species found in Indonesia have been designated as ETP species. This research aims to test the efficacy of red LED Cree lights in BSC bottom gillnet fisheries to reduce horseshoe crabs bycatch. The experimental fishing approach was employed in the waters of Ambulu Village, Cirebon Regency, with 17 trips as replication. Two sets of gillnets, as control and treatment (equipped with LED lights), respectively, were utilized in the study. Data collected were the number of species and individuals of targeted species (BSC) and horseshoe crab as bycatch resulting from the BSC gillnet operations in both control and treatment nets. A descriptive analysis was used for catch composition. Statistical analyses, including paired sample t-tests and Wilcoxon tests, were conducted on the horseshoe crab bycatch and BSC catch data to test differences between the control and treatment nets. The most abundant catch consisted of crab (Actaeodes tomentosus), with 82 individuals captured in the treatment nets and 87 in the control nets. Blue swimming crab (Portunus pelagicus) caught 76 and 53 individuals in the treatment and control nets, respectively. The bycatch of horseshoe crabs (Limulidae) in the treatment and control nets of 10 and 27 individuals, respectively. The analysis revealed that the BSC catch in the treatment nets did not significantly differ from that in the control nets. Conversely, a significant difference was observed in the horseshoe bycatch between the treatment and control nets. Incorporating red LED Cree lights resulted in a 35.79% increase in the BSC catch and a 62.96% reduction in the horseshoe bycatch.